Phytochemical Screening and In Silico Prediction of Gynura divaricata Ethanolic Extract as A Potential PIM-1 Inhibitor: Phytochemical and In Silico Prediction of Gynura divaricata - Puspitarini , Sapti; Hermanto, Feri Eko; Rohim, Abd; Dliyauddin, Moh; Hendratmoko, Ahmad Fauzi; Budiyanto, Mohammad; Ilhami, Fasih Bintang (Journal of Tropical Life Science, 2026)
The pharmacological properties and traditional uses of medicinal plants often correlate with their bioactive constituents, which contribute to diverse therapeutic effects, including anticancer activity. Cancer remains one of the leading causes of mortality worldwide, and the discovery of novel anticancer agents from natural sources continues to be an important research focus. Gynura divaricata is a medicinal herb widely used in traditional Asian medicine for treating diseases. Recent studies have reported that G. divaricata contains several bioactive compounds. such as flavonoids, phenolic acids, terpenoids, and alkaloids, which are known for their antioxidant and anticancer properties. However, despite its traditional use and pharmacological potential, the molecular mechanisms underlying the anticancer activity of G. divaricata remain poorly understood. This study aimed to screen the phytochemical content of the ethanolic leaf extract of G. divaricata and to predict its potential anticancer activity through computational analysis targeting the PIM-1 protein. The DPPH inhibition, total flavonoid content, and total phenolic content of the extract were evaluated. Phytochemical profiling was performed using LC-HRMS. Molecular docking and molecular dynamics simulations were conducted to predict the interactions between the active compounds of G. divaricata and the PIM-1 protein. The extract exhibited 50% DPPH inhibition at a concentration of 2071.01 ppm, with total flavonoid and total phenolic contents of 107.44 ± 4.41 mg QE/g and 10.96 ± 0.49 mg GAE/g, respectively. Identified bioactive compounds, including curcumin, (+)-ar-turmerone, and 4-coumaric acid, were further analyzed through molecular docking to assess their interactions with the PIM-1 kinase. The docking results revealed that these compounds showed favorable binding affinities to the active site of PIM-1, suggesting their potential as anticancer agents. This study is the first to report the potential of G. divaricata active compounds as PIM-1 inhibitors, warranting further validation through both in vitro and in vivo studies.